Território e desenvolvimento: um estudo a partir do Canal do Sertão em Inhapi Alagoas - Carmo, Wellington Silva do (2018)
The Adductor Canal do Sertão Alagoano is an enterprise that from its beginning generates hope for the population of the Alagoan semi-arid. The speech coming from the public power always presents it as the solution to the problems of the region and attributes them to the phenomenon of drought. From this point of view the work is posed as a great promoter of the development of the semi-arid region of Alagoas. The present research sought to investigate how the implementation of the Canal do Sertão in the municipality of Inhapi-AL has been taking place. For that, the proposals presented by the Feasibility Study of the Water Resources of the Sertão Alagoano Project, the Inhapi I Perimeter I Basic Project and the Rural Development Plan for the Sertão Canal were analyzed. In addition, field research was carried out at the agencies responsible for agriculture in the municipality of Inhapi. With this we seek to confront what is proposed and what has been developed around the enterprise and whether it is serving the population in its surroundings or serves purposes other than those promised by the official discourse.